2005
DOI: 10.1002/micr.20097
|View full text |Cite
|
Sign up to set email alerts
|

Dose response of enoxaparin at the cremaster muscle flap microcirculation

Abstract: The effects of different dosages of enoxaparin (Lovenox), a low molecular-weight heparin, on microcirculation were investigated. The cremaster muscle model for intravital microscopy was used. Four groups were studied: in group I (n = 6), the controls no agent was given; in group II (n = 6), enoxaparin (2 mg/kg s.c.), in group III, (n = 6), enoxaparin (4 mg/kg s.c.); and in group IV, (n = 6), exoxaparin (8 mg/kg s.c.). These agents were injected before muscle dissection. All animals were observed under intravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The ROS in the pancreatic tissues were significantly higher in CRL-induced rats than in the control animals in our study, and our results conform to those previously reported in literature (4,8,24). This study demonstrates the powerful therapeutic potential of the concomitant use of 2 agents-HES (17)(18)(19) and ENX (12,13,15)-that are clinically applied for their anticoagulant or anti-inflammatory properties. To our knowledge, ours is the first study where HES was used to treat acute pancreatitis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ROS in the pancreatic tissues were significantly higher in CRL-induced rats than in the control animals in our study, and our results conform to those previously reported in literature (4,8,24). This study demonstrates the powerful therapeutic potential of the concomitant use of 2 agents-HES (17)(18)(19) and ENX (12,13,15)-that are clinically applied for their anticoagulant or anti-inflammatory properties. To our knowledge, ours is the first study where HES was used to treat acute pancreatitis.…”
Section: Discussionsupporting
confidence: 92%
“…ENX is a lowmolecular-weight heparin that is widely used in surgery. ENX is a potent vasodilator, and it inhibits platelet aggregation and thrombosis, increases capillary permeability and perfusion effectively, and scavenges ROS considerably (12)(13)(14)(15)(16). There is no consensus in literature concerning the effects of anticoagulants in inflammation and pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…34 Lower doses (2 mg/kg) of subcutaneous LMWH (enoxaparin) were most effective at dilating capillaries (by 33%) without bleeding complications in an animal model. 53 Ertas et al 53 reported significant capillary dilation in rat cremaster muscle 5 hours after administration of 2 mg/kg and 4 mg/kg LMWH. The efficacy of higher LMWH doses (8 mg/kg) was no different than control, but caused markedly increased bleeding.…”
Section: Low Molecular Weight Heparinsmentioning
confidence: 98%
“…17,20 The doses and treatment duration were chosen based on previous studies on this subject, to obtain a better comparison. 21,22 The pathophysiology of necrosis due to ischemia is complex, involving vascular insufficiency as a consequence of arterial vasospasm mediated by vasoactive substances, production of free radicals, swelling of endothelial cells, inactivation of sodium and potassium pumps, and thrombotic venous congestion. 4,23 Two important mechanisms have been implicated in postsurgical damage: neutrophilic influx and vascular thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Enoxaparin has potent anticoagulant activity, with a lower propensity for bleeding than unfractionated heparin. 21 Low-dose enoxaparin also exerts anti-inflammatory effects in animal models and in humans, so its therapeutic effects may be attributable to a combination of anticoagulant and anti-inflammatory properties. 10 However, some researchers maintain that its anticoagulant activity is key, based on microcirculatory changes.…”
Section: Discussionmentioning
confidence: 99%